Functional (Psychogenic) Neurological Disorders: Assessment and Acute Management in the Emergency Department - Anderson, Jordan R.; Nakhate, Vihang; Stephen, Christopher D.; Perez, David L. (Seminars in Neurology, 2019)
Functional neurological disorders (FND) are complex and prevalent neuropsychiatric conditions. Importantly, some patients with FND develop acute onset symptoms requiring emergency department (ED) evaluations. Historically, FND was a “rule-out” diagnosis, making assessment and management in the ED difficult. While the rapid triage of potential neurological emergencies remains the initial task, advancements have altered the approach to FND. FND is now a “rule-in” diagnosis based on validated neurological examination signs and semiological features. In this perspective article, we review signs and semiological features that can help guide the initial assessment of FND in the acute setting. Thereafter, we outline potential approaches to introduce a suspected diagnosis of FND to patients in the ED, while emphasizing the need for a comprehensive neurological evaluation. Physical and occupational therapy may be useful adjunct assessments in some individuals. Notably, clinicians in the ED setting are important members of the interdisciplinary approach to FND.
Keywords: conversion disorder; psychogenic nonepileptic seizures; functional movement disorders; functional paralysis